Effect of medium solvents on crystalline degree and specific surface area of Cu3BiS3nanoparticles synthesised by biomolecule-assisted hydrothermal and solvothermal methods - K. Aup-Ngoen (2018)
Copyright © 2017 Inderscience Enterprises Ltd. Cu 3 BiS 3 nanoparticles were successfully synthesised by hydrothermal and solvothermal methods using L-cysteine biomolecules as a sulphur source and complexing agent. Phase and purity of the samples were characterised by X-ray diffraction (XRD) and selected area electron diffraction (SAED). Scanning and transmission electron microscopy (SEM and TEM) revealed the increasing of particle size from 29.8 ± 6.3 nm to 89.6 ± 17.2 nm by changing the medium solvents from de-ionised (DI) water to ethylenediamine (EN), in accordance with the decrease in the BET surface area from 17.5560 ± 0.1170 m 2 /g for the DI particles to 4.0297 ± 0.0370 m 2 /g for the EN particles. The absorption spectrum of highly crystalline Cu 3 BiS 3 nanoparticles synthesised in EN was used to determine the direct energy gap (E g ) which was found to be 1.6 eV. In this research, a formation mechanism is proposed and discussed according to the experimental results.